2020
DOI: 10.1155/2020/9510305
|View full text |Cite
|
Sign up to set email alerts
|

Camelina sativa Methanolic and Ethanolic Extract Potential in Alleviating Oxidative Stress, Memory Deficits, and Affective Impairments in Stress Exposure-Based Irritable Bowel Syndrome Mouse Models

Abstract: Camelina sativa is mainly used as an oilseed crop; its edible oil is being also used as a traditional home remedy for the treatment of ulcers, wounds, and eye inflammations, due to the antioxidant activities. In the present study, the chemically characterized alcoholic extracts of Camelina sativa var. Madalina defatted seeds (5 g/kg body weight p.o., suspended in CMC-Na 0.1%) were administered to stress-induced animal models of irritable bowel syndrome (based on combinations of contention stress and multifacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Methanolic and ethanolic extracts of C. sativa seeds show significant antibacterial and antifungal activities and potential as natural preservatives [ 287 ]. Additional therapeutic properties are associated with phenolic compounds in C. sativa seeds and oil, such as chlorogenic, caffeic, sinapinic, and phytic acids [ 288 ]. However, as mentioned earlier, C. sativa seeds contain glucosinolates, which have antinutritive properties [ 201 ].…”
Section: Uses Of C Sativamentioning
confidence: 99%
“…Methanolic and ethanolic extracts of C. sativa seeds show significant antibacterial and antifungal activities and potential as natural preservatives [ 287 ]. Additional therapeutic properties are associated with phenolic compounds in C. sativa seeds and oil, such as chlorogenic, caffeic, sinapinic, and phytic acids [ 288 ]. However, as mentioned earlier, C. sativa seeds contain glucosinolates, which have antinutritive properties [ 201 ].…”
Section: Uses Of C Sativamentioning
confidence: 99%
“…Finally, it is interesting to note that methanolic and ethanolic extract of Camelina sativa were able to alleviate oxidative stress, memory deficits, and affective impairments in a mouse model of irritable bowel syndrome caused by stress exposure [ 32 ]. Altogether, these findings suggest the possibility of a synergic effect of Camelina sativa constituents on visceral pain and comorbidities associated with colitis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, camelina seeds are a source of GSLs like glucoarabin and glucocamelinin [ 29 , 30 , 31 ], though the in vivo biological effects of these phytochemicals are still largely unknown. Recent evidence from the literature showed that Camelina sativa seed alcoholic extracts can ameliorate cognitive performance, as well as mood, and exert an antioxidant effect in both the brain and gut in a mice model of IBS [ 32 ], though the effect on visceral pain was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, our group previously studied the antioxidant potential of Camelina sativa. We showed that the oil obtained from the Camelina seeds could improve antioxidant enzyme activity and prevent lipid peroxidation in a rat model of stress exposure (IBS model) [120]. Moreover, Mierina et al [121] showed that the antioxidant potential is also preserved by the seed cakes, not only the oil.…”
Section: Antioxidantsmentioning
confidence: 96%